Characterization of Cellulomonas sp. HM71 as potential probiotic strain for human health - Yadav, Monika; Kumar, Tarun; Maurya, Ranjeet; Pandey, Rajesh; Chauhan, Nar Singh (Frontiers in Cellular and Infection Microbiology, 2023)
Cellulomonas sp. HM71, a human gut microbe possesses metabolic machinery to catabolize antigenic gluten, hence, holds promises as microbial therapy to treat gluten-derived celiac disease. However, its efficacy, safety, and survivability in the gastrointestinal ecosystem await functional elucidation. The current study is designed to characterize Cellulomonas sp. HM71 for its physiological, genomic, and probiotic properties. The morphological and physiological assessment indicates it as a coccus-shaped gram-positive bacterium growing optimally at 30°C in a neutral environment (pH 7.0). Cellulomonas sp. HM71 showed continuous growth even in stressful environments (salinity up to 3% NaCl and 6% KCl), variable temperature (25°C to 35°C) and pH (5-9), antibiotics, and gastric and intestinal conditions. The Cellulomonas sp. HM71 genome harbors diversified genetic machinery to modulate humongous metabolic potential for the host. This was substantiated by the hemolytic and CaCo-2 cell line assay which confirms its cellular adherence and biosafety. Notably, genome analysis did not identify any pathogenic islands. Probiotic characterization indicates its potential to overcome waterborne infections and digestion-related disorders. Cumulatively, Cellulomonas sp. HM71 can be considered a probiotic strain for improving human health because of the highlighted functions.